Design and evaluation of transdermal drug delivery system of gliclazide - Shinde, Anilkumar J; Shinde, Amit L; More, Harinath N (Asian Journal of Pharmaceutics (AJP), 2014)
Transdermal systems are ideally suited for diseases that demand chronic treatment. Hence, an anti-diabetic agent of both therapeutic and prophylactic usage has been subjected to transdermal investigation. Gliclazide, a second-generation hypoglycemic agent, faces problems like its poor solubility, poor oral bioavailability with large individual variation and extensive metabolism. In the present work, transdermal matrix-type patches were prepared by film casting techniques on mercury using polymers like HPMC, Eudragit RL-100, and chitosan. Also an attempt was made to increase the permeation rate of drug by preparing an inclusion complex with hydroxypropyl Î²-cyclodextrin (HP Î²-CD).The possibility of a synergistic effect of chemical penetration enhancers (CPE) (propylene glycol and oleic acid) on the transdermal transport of the drug was also studied. Folding endurance was found to be high in patches containing higher amount of the Eudragit. There was increase in tensile strength with an increase in Eudragit in the polymer blend. In vitro drug release profile indicates that the drug release is sustained with increasing the amount of Eudragit in patches.The patches containing inclusion complex of drug showed higher permeation flux compared with patches containing plain drug. The result of the synergistic effect indicates that the HP Î²- CD in conjunction with other CPE showed a higher permeation flux.